2018
DOI: 10.21836/pem20180405
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear scintigraphic retrospective study of the C6/7 articular facets of the equine cervical spine

Abstract: The objectives of this study were firstly, to determine an objective grading system of radiopharmaceutical uptake in the C6/7 articular facets of the cervical spine as a predictor of clinical signs in warmblood sporthorses; and secondly to establish an objective absorption coefficient (AC) value that could possibly differentiate between presence or absence of clinical signs in this region. 308 scintigraphic views of the cervical spine in 154 German warmblood horses were evaluated. Scintigrams were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…37 The current study confirmed a clinically 'significant' IRU in the articular processes of C6/C7 using the AC. 25 In the survey conducted by Gerlach et al, 25 the coefficient had the most significant value for sports horses aged between 11 and 15 years. Since 84% of the study population consisted of dressage or show jumping horses with a median age of 9 years, the AC was considered suitable to define areas of IRU, representing pathological and possibly clinically significant changes in the articular processes of C6/C7.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…37 The current study confirmed a clinically 'significant' IRU in the articular processes of C6/C7 using the AC. 25 In the survey conducted by Gerlach et al, 25 the coefficient had the most significant value for sports horses aged between 11 and 15 years. Since 84% of the study population consisted of dressage or show jumping horses with a median age of 9 years, the AC was considered suitable to define areas of IRU, representing pathological and possibly clinically significant changes in the articular processes of C6/C7.…”
Section: Discussionmentioning
confidence: 96%
“…The scintigraphic appearance of cervical vertebrae is also reported to be highly variable in horses lacking clinical evidence of cervical dysfunction, depending on the age and use of the animal, the size of the articular processes and the thickness of the surrounding soft tissue layers. 17,25,36 Other authors consider an IRU at C6/C7 as an abnormal finding, regardless of clinical signs. 37 The current study confirmed a clinically 'significant' IRU in the articular processes of C6/C7 using the AC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations